Analysis of the Impact of Trading Liquidity on the Development of Investment Time Horizon on the Example of the Warsaw Stock Exchange - Gniadkowska-Szymańska, Agata (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
The importance of liquidity has been acknowledged for a long time now. Liquidity is defined as the ease with which an asset can be converted into cash. A considerable number of studies investigated stock liquidity providing evidence that more illiquid stocks yield higher returns which include an illiquidity premium. According to Amihuda and Mendelson (1986b: 43–48), a required rate of return on the shares (gross, i.e. after taking into account the cost of liquidity) should increase with increasing liquidity, but the marginal increase should decrease with an increasing investment horizon, thus decreasing the likelihood of premature termination of the investment. As a result, investors with different investment horizons may require different rates of return per unit of time from the same shares (Huang 2003: 104–129). Investor horizon is the time period for which an investor holds a stock. Most of the research conducted on investment horizon links it to liquidity, supporting the thesis that it is negatively related to liquidity. “Transaction costs and the holding periods for common stocks” written by Atkins and Dyl (1997: 309–325) is one of the first papers to investigate the effects of liquidity on holding period. The aim of this study is to show the dependencies occurring between the phenomena of investment horizon and asymmetric information and the liquidity of shares of a company.